Efficacy and safety of empagliflozin in type 2 diabetes mellitus: a meta-analysis of randomized controlled trials. Issue 3 (3rd April 2017) - Devi, R.; Mali, Ghanshyam; Chakraborty, Indrani; Unnikrishnan, Mazhuvancherry Kesavan; Abdulsalim, Suhaj
ABSTRACT: Objectives: The prevalence of diabetes has increased in the recent decades and optimum glycemic control is required to reduce morbidity and mortality. We meta-analyzed randomized controlled trials in order to assess the efficacy and safety of empagliflozin compared to placebo in type 2 diabetes mellitus patients. Methods: We included double-blind, placebo controlled trials of empagliflozin that evaluated glycemic efficacy and safety (10 mg or 25 mg) either as monotherapy or as add-on to existing diabetes pharmacotherapy. Results: The results demonstrated significant improvements in HbA1c (SMD −0.929%, 95 % CI −1.064 to −0.793, for 10 mg and −1.064%, 95 % CI −1.184 to −0.944, for 25 mg) and FPG (SMD −0.929%, 95 % CI −1.064 to −0.793, for 10 mg and −1.064%, 95 % CI −1.184 to −0.944, for 25 mg) with empagliflozin monotherapy (n = 609) compared to placebo. Significant improvements in HbA1c [SMD −1.582%, 95% CI −2.164 to −1.000, for 10 mg (n = 1079) and −1.668%, 95% CI −2.260 to −1.077, for 25 mg (n = 1070)] and FPG [SMD −0.865 mmol/L, 95 % CI −1.309 to −0.420, for 10 mg (n = 854) and −0.996 mmol/L, 95% CI −1.456 to −0.536, for 25 mg (n = 854)] were also observed in empagliflozin add-on therapy trials. Reductions in blood pressure and body weight were also seen in both monotherapy and add-on therapy. Empagliflozin was associated with increased risk of hypoglycemia, genital and urinary tract infections (OR 1.043, 2.814, 1.119 respectively). Conclusion: This meta-analysis shows empagliflozin is safe and effective for the treatment of T2DM along with existing diabetes pharmacotherapy.